2014
DOI: 10.1122/1.4881467
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude oscillatory shear and Fourier transform rheology analysis of branched polymer melts

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…We deconvoluted the total stress oscillation into an elastic oscillation and a viscous oscillation by considering the in phase and out of phase component of stress (Lauger and Stettin, 2010;Hoyle et al, 2014, Stadler et al, 2008, Carmona et al, 2014Ptaszek, 2015;Ewoldt and McKinley, 2010). The Lissajous-Bodwitch curves for the elastic component of stress are plotted in the form of normalized stress and normalized elastic stress vs. normalized strain for each frequency and for the four phases of dough mixing.…”
Section: Analysis Of the Rheological Behavior In The Linear And Nonlimentioning
confidence: 99%
“…We deconvoluted the total stress oscillation into an elastic oscillation and a viscous oscillation by considering the in phase and out of phase component of stress (Lauger and Stettin, 2010;Hoyle et al, 2014, Stadler et al, 2008, Carmona et al, 2014Ptaszek, 2015;Ewoldt and McKinley, 2010). The Lissajous-Bodwitch curves for the elastic component of stress are plotted in the form of normalized stress and normalized elastic stress vs. normalized strain for each frequency and for the four phases of dough mixing.…”
Section: Analysis Of the Rheological Behavior In The Linear And Nonlimentioning
confidence: 99%
“…However, it has been demonstrated that linear rheology alone is insufficient to unambiguously distinguish different branching topologies. Others have proposed using nonlinear oscillatory rheology and extensional rheology for this purpose [20,21]. Although advances in the understanding of the rheology in various chemically branched polymers may aid in understanding the role of branching in WLM rheology and vice versa, the critical differences in the stress-bearing nature of the branching between these different systems must be carefully considered when making comparisons.…”
Section: Relationship To Polymer Solutions and Meltsmentioning
confidence: 99%
“…There are various kinds of standard flows [1][2][3] to study the rheological properties of non-Newtonian fluids which all are similar in basics. In these methods, a material is subjected to defined stress or strain, and then, its response to the imposed stress or strain is measured.…”
Section: Introductionmentioning
confidence: 99%